2022
DOI: 10.1186/s12913-022-07669-0
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to routine intimate partner violence screening in antenatal care settings in Uganda

Abstract: Background Uganda clinical guidelines recommend routine screening of pregnant women for intimate partner violence (IPV) during antenatal care (ANC). Healthcare providers play a critical role in identifying IPV during pregnancy in ANC clinics. This study explored facilitators and barriers for IPV screening during pregnancy (perinatal IPV screening) by ANC-based healthcare workers in Uganda. Methods We conducted qualitative in-depth interviews among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Healthcare responses to survivor needs may be challenging. Prior research shows that facility-based clinicians, especially in rural settings, often do not routinely screen for IPV among healthcare seeking individuals (11). Women are already reluctant to report abuse because it violates gender norms of the ideal wife, or because they fear that their partners will become more violent or retaliate nancially.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare responses to survivor needs may be challenging. Prior research shows that facility-based clinicians, especially in rural settings, often do not routinely screen for IPV among healthcare seeking individuals (11). Women are already reluctant to report abuse because it violates gender norms of the ideal wife, or because they fear that their partners will become more violent or retaliate nancially.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the initial response to IPV reported to healthcare providers involves managing the immediate medical emergencies and safety related issues. Non-disclosure of IPV is compounded by barriers to routine IPV screening by healthcare workers such as inadequate sta ng levels, limited privacy, lack of provider IPV awareness and comprehensive GBV prevention and response training (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-income countries, the rate of IPV screening is low when compared to the rates in high income countries. In Uganda, Kenya, and South Africa, health professionals do not always screen pregnant women for IPV [ [17] , [18] , [19] ]. Anguzu et al [ 18 ], found that 11 out of 28 health professionals screened pregnant women for IPV.…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, Kenya, and South Africa, health professionals do not always screen pregnant women for IPV [ [17] , [18] , [19] ]. Anguzu et al [ 18 ], found that 11 out of 28 health professionals screened pregnant women for IPV. The screening rate is moderately low when compared to the total health professionals that were interviewed.…”
Section: Introductionmentioning
confidence: 99%